CYBERSECURITY AWARENESS LEVELS IN THE DIGITAL AGE: A STUDY OF UNIVERSITY STUDENTS - Md Kasim, Mohd Fazzly Rassis; Wan Abu Bakar, Wan Hashridz Rizal; Mohamad, Zuraini; Kamarozaman, Zarina (Jurnal 'Ulwan, 2025)
This study investigates university students' cybersecurity awareness in the context of increasing digital threats. As one of the most active user groups in cyberspace, students' level of knowledge is crucial to ensure online safety and reduce human-related vulnerabilities. Using a cross-sectional survey design and convenience sampling, data were collected from 142 respondents through a five-point Likert scale that assessed their familiarity with cybersecurity practices and terminology. The analysis revealed a high overall awareness level (Mean = 4.656, SD = 0.792), particularly among students aged 18–24. However, slightly lower awareness was observed among those aged 25–34, indicating the need for targeted educational efforts. While the findings offer valuable insights, the limited sample size restricts the generalizability of the results. Therefore, future studies should include a more diverse and extensive sample to reflect broader trends. The study underscores the importance of practical training and age-responsive cybersecurity programs to strengthen digital resilience among university students.